Self-Regulation and Rhetorical Problem Solving: How Graduate Students Adapt to an Unfamiliar Writing Project. (July 2019) - Roderick, Ryan
Research on writing and transfer has shown that writers who have sophisticated rhetorical knowledge are well equipped to adapt to new situations, yet less attention has been paid to how a writer's adaptability is influenced by their writing processes. Drawing on Zimmerman's sociocognitive theory of self-regulation, this study compared the writing processes taken up by graduate student writers composing a research proposal for their final project in a tutor-training practicum. Findings from process logs, interviews, and drafts differentiated self-regulation strategies associated with varying degrees of success. The more successful writers framed problems in terms of potential solutions, used problems to set goals, and reacted to problems by creating a narrative of progress; in contrast, less successful writers avoided problems or framed them as dead-ends. Compared to the less successful writers, the more successful writers concluded the project with robust knowledge about research proposal writing. These findings suggest that self-regulation strategies may be linked to an ability to develop rhetorical knowledge and practices in the face of challenging writing situations.